Penyuluhan Kesehatan Tentang Pentingnya Imunisasi Di Puskesmas Antang Kota Makassar - Rosdiana, Rosdiana; Saide, Rusnaeni; Pannyiwi, Rahmat; Malaha, Naomi; M, Sakriawati (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2023)
Immunization is an effort to actively create/increase a person's immunity against a disease so that if one day they are exposed to that disease they will not get sick or only experience mild illness. The low level of complete basic immunization coverage is still a very difficult problem to face. The government's program in an effort to improve children's health status is that before the child is one year old, basic immunization should be given completely according to his age. In this condition, it is hoped that the immune system can work optimally with minimal side effects. The aim of this service is to increase public knowledge about complete basic immunization so that basic immunization coverage can increase. The methods used are lectures and discussions. This service was carried out in the working area of the Batua Community Health Center, Makassar City with a total of 30 mothers participating. From the results of this counseling, there was an increase in mothers' knowledge and understanding, so it is hoped that this training activity can be implemented in all health center work areas with government support.